Meal skipping among patients with type 2 diabetes mellitus (T2DM) and its associations with glycaemic control, eating out of home and binge eating - Hizlinda Tohid,; Ooi, CF; Leong, YH; Mohamad Ngasri NE,; Ismail MI,; Mohamad Alwi SNN,; Jafri NNA,; Ezura Madiana Md. Monoto, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Meal skipping is a common way to restrict diet, but its practice by patients with type 2 diabetes mellitus (T2DM) remains undetermined due to the scarcity of the research. The main aim of this study was to assess how common patients with T2DM skipped meals. Its associations with sociodemographic and clinical characteristics, HbA1c, eating out of home and binge eating were examined too. This cross-sectional study was conducted in 2015 among 203 patients at a public healthcare clinic in Kuala Lumpur. A self-administered questionnaire including the Malay-version Binge Eating Scale was used. The proportions of participants who frequently skipped meals and ate out of home were 41.4% and 61.6%, respectively. Only 2% of them had binge eating disorder. Multiple logistic regression showed only Chinese was significantly associated with frequent meal skipping compared to Malay (adjusted odds ratio: 0.36; 95% confidence interval: 0.16-0.77; p value= 0.009) after controlling for age, employment status, educational status, HbA1c, presence of complication, type of treatment, eating out of home and binge eating. In conclusion, meal skipping was a frequently practised eating behaviour. Eating out of home was common too, but binge eating was rare. Meal skipping was not influenced by both eating practices and it had insignificant associations with glycaemic control. Cultural and religious factors may play an important role in defining their eating practice. Further studies are needed to assess the safety and acceptability of this practice, but clinically, its effects must be individually examined to prevent unwanted consequences on their health.